l’étude Génétique de la pigmentation de la robe chez les bovins Région de djidiouia - SAADAOUI, Abed (My University, 2021)
Our study was carried out in the region of Djidiouia wilaya of Relizane in the farm of Mr HAMRI Mostefa, it is part of the characterization of the color of the coat in cattle by the principle of examining the profile of adult animals and their progeny using phenotypic profiling on a total number of 147 bovine heads comprising two breeds (100 Holsteins * 60 black magpie 40 red magpie *, 47 montbéliarde). The results showed by the genotypic frequency calculations (Holstein "Pie noir 60%", "Pie rouge 40%" and the Montbéliarde she is 100% "Pie rouge") and the Holstein allelic frequency (the ED allele = 0.60, the e allele = 0.40 and the e Montbéliarde allele = 1 and on the inheritance of the color between progenies and their parent, it can be seen that the effects of the ED allele completely mask the effects of the e allele. These results reveal that coat color is a qualitative trait influenced by a small number of genes and of little economic interest.
Keywords: Race, Bovin, Robe, alleles, genes, Djidiouia. Relizane